(untitled) (Global Journal of Human-Social Science, 2024)
The Study Titled Consideration of Benefits Maslahah and Harm Mafsadah in Child Marriage Cases in Malaysia from the Perspective of Maqasid Al-Syariah Aims to Examine the Practice of Child Marriage in Malaysia by Analyzing its Alignment with the Principles of Maqasid Al- Syariah Particularly in Balancing the Benefits and Harms The Practice Prevalent in Certain Communities Raises Significant Concerns Related to Children s Rights Education and Long- Term Well-Being The Primary Objective of This Research is to Investigate Whether Child Marriages Fulfill the Objectives of Islamic Law Which Emphasizes the Protection of Religion Life Intellect Lineage and Wealth Using a Qualitative Approach this Study Relies on Document Analysis and In- Depth Interviews with two Industry Practitioners in the State Religious Department in Selangor and Pahang the Socio- Economic Religious and Cultural Justifications for Child Marriage The Findings Suggest that While Certain Benefits Such as Avoiding Illicit Relationships Are Considered The Overall Harms Including the Potential for Physical and Psychological Harm to Children Outweigh the Perceived Benefits The Study Concludes that Child Marriages Often Fail to Meet the Core Objectives of Maqasid Al-Syariah Particularly in Safeguarding Health Intellect and Future Potential The Implications of this Research Suggest that there is a Pressing need for Legislative Reform and Enhanced Public Awareness to Protect Children s Rights and Well-Being Aligning the Legal Framework with the Higher Objectives of Islamic Law